(untitled) (International Journal of Engineering and Computer Science, 2015)
The credit card has become the most popular mode of payment for both online as well as regular purchase, in cases of fraud associated with it are also rising. Credit card frauds are increasing day by day regardless of various techniques developed for its detection. Fraudsters are so experts that they generate new ways of committing fraudulent transactions each day which demands constant innovation for its detection techniques. Most of the techniques based on Artificial Intelligence, Fuzzy Logic, Neural Network, Logistic Regression, Naïve Bayesian, Machine Learning, Sequence Alignment, Decision tree, Bayesian network, meta learning, Genetic programming etc., these are evolved in detecting various credit card fraudulent transactions. This paper presents a survey of various techniques used in various credit card fraud detection mechanisms.